Events Across the Life Course Contribute to Higher Mobility Impairment Rates in Rural U.S. - Ipsen, Catherine; Ward, Bryce; Myers, Andrew (Frontiers in Rehabilitation Sciences, 2022)
Purpose: This paper investigates how life events such as injuries, health insurance coverage, geography, and occupation contribute to mobility disability rates over time. Findings can inform policies and practices to address factors that may contribute to disability in rural and urban areas. Methods: We utilized 27 waves of the National Longitudinal Survey of Youth (NLSY) data from 1979 to 2016 to explore how past injury, occupation, health insurance coverage, and rurality predicted mobility impairment at ages 40 and 50 using regression analysis. Findings: Rural respondents reported significantly higher rates of mobility impairment at age 40 and age 50 relative to people living in urban areas, and were more likely to report injury, work in high exertion occupations, and experience several pain-related health conditions. Using logistic regression and controlling for race and education, we found that people had higher odds of experiencing mobility impairment at age 40 if they reported a broken bone in the last 10 years, reported ever being knocked unconscious, had any workplace injury from 1988-2000, or lived in a rural area. People reported lower odds of mobility impairment if they had more consistent health insurance coverage over time. Further analysis showed that people consistently uninsured over time were 91% more likely to report mobility impairment at age 40 than those consistently insured. Conclusion: A better understanding of environmental factors associated with disability such as access to insurance, risk exposures, resources, and other place-based behaviors can inform additional strategies for reducing the severity and duration of mobility disability.